Diagnostic value of urine Gram staining for urinary tract infection in children - I Nyoman Sartika; Ketut Suarta; Pungky Ardhani (Indonesian Pediatric Society, 2009)
Background Urine culture is the standard procedure for diagnosisof urinary tract infection (UTI). To reduce the cost and timespent in examining cultures, several rapid methods have beendeveloped including microscopic examination, chemical tests,and automated systems.Objective To determine the value of microscopic examination of a Gram stained uncentrifuged drop of urine for diagnosis of UTI.Methods We carried out a diagnostic test in Sanglah Hospital,Denpasar, from January 2007 to December 2007. Midstream urine specimens were Gram stained and then examined using a high power oil immersion lens. Twenty fields of view were examined and finding of two or more microorganisms was taken as positive result. Urine was also cultured and a yield of more than 105 CFU/ml was taken as positive result. The sensitivity, specificity, and predictive values of Gram stained urine were determined using urine culture as gold standard.Results From 43 subjects in our study, 12 subjects (28%) hadpositive urine culture. The prevalence was higher in males (58%)than females. UTI was most commonly caused by Klebsiellapneumoniae (33%). The sensitivity, specificity, positive predictivevalue, and negative predictive valuey, of the urine Gram stainwere 67% (95%CI 40 to 93), 9.7% (95%CI 91 to 100), 89%,88%, respectively. The accuracy, positive likelihood ratio, negative likelihood ratio, and post-test probability of the urine Gram stain were 88, 21, 0.3, and 89%, respectively.Conclusion Microscopic examination of Gram stained uncentrifuged drop of urine is specific and accurate, but not sensitive for the diagnosis of UTI.